Aplikasi Gojek di Mata Mahasiswa: Analisis Pengaruh Social Media dan Brand Image pada Keputusan Penggunaan - Pratama, Saka (Economie: Jurnal Ilmu Ekonomi, 2025)
This journal reviews how social media and brand image can influence consumer decisions in using Gojek. This research focuses on how social media promotion and consumer views on Gojek have an impact on customer decisions to use Gojek. The target of this journal is to investigate The social media and brand image effect on customer decisions in using The Gojek application. This study uses quantitative research methods by distributing questionnaires to 120 respondents who use The Gojek application. The sample was determined using The Slovin formula with 55 respondents representing The population. The study data was processed using multiple linear regression with The help of The SPSS 26 application. The results found that social media and brand image have a positive influence on consumer decisions in using The Gojek application. According to The coefficient of determination, it means that 63% of consumer decisions in using The application are influenced by social media and brand image, while The remaining 37% is influenced by various oTher factors outside The two research variables. Based on These findings, it is recommended that Gojek continue to strengThen digital communication strategies through social media that are up to date and informative, maintain and improve and enhance a positive brand image in The eyes of consumers.